Performance optimization of an air source heat pump water heater using mathematical modelling - Tangwe, Stephen; Simon, Michael; Meyer, Edson L.; Mwampheli, Sampson; makaka, Golden (Journal of Energy in Southern Africa, 2015)
In South Africa, there is an ongoing constraint on the electricity supply at the national grid to meet the demand. Eskom is implementing various measures such as the Integrated Demand Management and the promotion and encouragement of the use of energy efficient devices like an Air Source Heat pump (ASHP) water heater to replace the high electrical energy consuming conventional geysers for sanitary hot water production. The ASHP water heater market is fast gaining maturity. A critical mathematical model can lead to performance optimization of the systems that will further result in the conservation of energy and significant reduction in global warming potential. The ASHP water heater comprises of an ASHP unit and a hot water storage tank. In this study, a data acquisition system (DAS) was designed and built which monitored the energy used by the geyser and the whole building, the temperature at the evaporator, condenser, tank outlet hot water, tank inlet cold water, the ambient temperature and relative humidity in the vicinity of the ASHP evaporator. It is also worthy to mention that the DAS also included to a flow meter and two additional temperature sensors that measured the volume of water heated and inlet and outlet water temperature of the ASHP. This work focused on using the mathematical equation for the Coefficient of Performance (COP) of an ideal Carnot’s heat pump (CHP) water heater to develop basic computation in M-file of MATLAB software in order to model the system based on two reservoir temperatures: evaporator temperatures (Tevp) of 0°C to 40°C (approximated to ambient temperature, Ta) and condenser temperatures (TCon) set at 50°C, 55°C and 60°C (approximated to the hot water set temperature of 50°C, 55°C and 60°C) respectively. Finally, an analytical comparison of a CHP water heater to the practical ASHP water heater was conducted on a hot water set point temperature of 55°C. From the modelling results, it can be deduced that at 0°C Tevp, the COP was 5.96 and 2.63 for CHP and ASHP water heater respectively, at a hot water set temperature of 55°C. Above 20°C Tevp, the rate of change of COP increased exponentially for the ideal CHP system, but was constant at 0.01/°C for the practically modelled ASHP water heater.